The Impact of Chlorine Substituents on the Regioselectivity of Pd(0)-catalyzed Direct Arylation of Heteroaromatics - Petrov, Ivan (Université d'Ottawa / University of Ottawa, 2011)
The regioselectivity in Pd(0)-catalyzed direct arylation of pyrrole, thiophene, and indole can be improved by blocking some of the reactive sites with a chloride group, leading to increased yields of the desired regioisomers. Competition experiments and computational studies show that the blocking group also activates the substrates toward arylation. Due to the activated nature of chlorinated heteroaromatics, rare and sought after regioisomers, such as 3-arylthiophenes, can be obtained under mild conditions in good yields. Chlorine-bearing thiophenes arylated at C3 and C4 have the potential to undergo controlled regioregular polymerization under conditions developed in the field of polythiophene chemistry. Mechanistic studies support the hypothesis that the arylation of the substrates under investigation likely proceeds via the CMD transition state.
Keywords: direct arylation; chlorination; heteroaromatics; palladium catalysis